2016
DOI: 10.1136/annrheumdis-2016-209124.144
|View full text |Cite
|
Sign up to set email alerts
|

A7.13 Distinct expression of IL-36α, β, γ and their antagonists IL-36RA and IL-38 in psoriasis, rheumatoid arthritis (RA) and crohn’s disease (CD)

Abstract: Background and objectivesThe IL-36 family of cytokines comprises three agonists: IL-36α, IL-36β and IL-36γ, an antagonist: IL-36Ra, and IL-38: another potential IL-36 inhibitor. IL-36 agonists are highly expressed in skin and are involved in the pathogenesis of psoriasis, while antagonists limit uncontrolled inflammation. The expression and role of IL-36 cytokines in other chronic inflammatory diseases is currently debated. In this study, we compared the expression profile of IL-36 cytokines in psoriasis, RA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…This higher expression of IL‐36α in AA patients might be a crucial promoter of Th1 and Th17 autoimmune responses. Similar to our results, IL‐36α gene expression was up‐regulated in psoriatic lesions and was correlated with disease severity 5 . In fact, anti‐IL‐36 receptor monoclonal antibodies repressed skin inflammation and inflammatory mediators’ expression in psoriasiform mouse model 6 .…”
Section: No %supporting
confidence: 89%
“…This higher expression of IL‐36α in AA patients might be a crucial promoter of Th1 and Th17 autoimmune responses. Similar to our results, IL‐36α gene expression was up‐regulated in psoriatic lesions and was correlated with disease severity 5 . In fact, anti‐IL‐36 receptor monoclonal antibodies repressed skin inflammation and inflammatory mediators’ expression in psoriasiform mouse model 6 .…”
Section: No %supporting
confidence: 89%
“…Unsurprisingly, a number of studies have uncovered the involvement of IL-38 in several autoimmune diseases. 41 For instance, a prior study came across elevated IL-38 expression levels in mice with arthritis induced by collagen as well as in patients with RA, 42 and further suggested that IL-38 exerts anti-protective effects on cartilage and bone destruction in collagen-induced arthritis. Importantly, increased expression levels of IL-38 were previously reported in patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…In psoriasis, IL‐36 cytokines influence the cornification processes in the epidermis by acting on keratinocytes, induce the production of Th17‐ and Th1‐polarizing cytokines by myeloid dendritic cells and macrophages, and potently sustain neutrophil recruitment. In lesional psoriatic skin, IL‐36α, IL‐36γ and IL‐36Ra are indeed highly expressed 70,84 . Conversely, the antagonist IL‐38 is downregulated 85 .…”
Section: Interleukin‐36 In Skin Diseasesmentioning
confidence: 99%
“…The three splice variants of IL‐36 (IL‐36α, IL‐36β and IL‐36γ) are potent proinflammatory cytokines, mainly produced in barrier sites of the body (cutaneous, bronchial and intestinal epithelium) 69 . In the skin, IL‐36γ is predominantly expressed in epidermal keratinocytes 70,71 . These cytokines play a first‐line defensive role against exogenous insults and contribute to maintaining cutaneous homeostasis.…”
Section: Interleukin‐36 In Skin Diseasesmentioning
confidence: 99%